The Quality of Pre-Service Teachers’ Instructional Module Projects: Constructive Alignment Principles - Endang Mastuti Rahayu; Armelia Nungki Nurbani; Nico Irawan; Komm Pechinthorn (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2026)
Instructional modules developed by pre-service teachers are expected to demonstrate coherent alignment among learning outcomes, instructional activities, and assessment tasks. However, previous studies suggest that student-generated instructional products often prioritize structural completeness over pedagogical coherence, resulting in weak integration of key instructional components. This study aimed to evaluate the pedagogical quality of pre-service teachers’ instructional modules through the lens of constructive alignment and to identify recurring patterns of alignment and misalignment. Employing a qualitative document analysis with a rubric-based evaluative approach, the study analyzed eighteen instructional modules developed by fifth-semester students in an English Language Education program at a private university in Surabaya, Indonesia. The analytical rubric examined the alignment among Intended Learning Outcomes (ILOs), Teaching and Learning Activities (TLAs), Assessment Tasks (ATs), cognitive levels based on Bloom’s Taxonomy, instructional models, and the integration of the Pancasila Student Profile. The findings showed that 77.8% of the modules demonstrated high alignment, 16.7% showed partial alignment, and 5.5% exhibited low alignment. Highly aligned modules displayed coherent relationships among learning objectives, instructional activities, and authentic assessment practices, particularly through student-centered approaches such as Project-Based Learning and Discovery Learning. Nevertheless, recurring weaknesses were identified in the formulation of measurable objectives, explicit cognitive-level mapping, and the development of analytic assessment rubrics. The study highlights the value of constructive alignment not only as a design principle but also as an evaluative framework for assessing pedagogical coherence in student-generated instructional products. The findings further underscore the need for practice-oriented scaffolding and assessment literacy training to strengthen pre-service teachers’ instructional design competence.